2018
DOI: 10.1111/iwj.12901
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to support pressure injury best practices by the inter‐professional team: A systematic review

Abstract: Optimal pressure injury (ulcer) management by the inter-professional team requires appropriate health care system and organisational resources, infrastructure, and policies. A systematic review was conducted on pressure injury care-related education and health care system-/organisation-level strategies. A search for relevant articles published between January 2006 and October 2014 was applied to 8 databases. Ultimately, 22 articles pertaining to education and training and 12 articles pertaining to health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…For example, online training from available sources such as the Wound, Ostomy and Continence Nurses Society Wound Treatment Associate (WTA) course may be an avenue for educating a broader array of inpatient providers that the hospitalists evaluated in this QI project. Like findings identified from Suva's work, our project found that providers wanted online learning tools 20 . Also, research has shown that e-learning tools have been effective in the management of wounds, specifically PIs 21 .…”
Section: Discussionsupporting
confidence: 66%
“…For example, online training from available sources such as the Wound, Ostomy and Continence Nurses Society Wound Treatment Associate (WTA) course may be an avenue for educating a broader array of inpatient providers that the hospitalists evaluated in this QI project. Like findings identified from Suva's work, our project found that providers wanted online learning tools 20 . Also, research has shown that e-learning tools have been effective in the management of wounds, specifically PIs 21 .…”
Section: Discussionsupporting
confidence: 66%
“…64,169,[176][177][178] Although the evidence may be relatively weak, effective multidisciplinary communication is likely to lead to better care. 179 A number of expert international, national and local guidelines have been produced specific to the main wound aetiologies and to processes in the wound management pathway and as general guidelines that cover most major wound types. Health professionals should refer to these guidelines, appropriate to their health-service delivery, for best practice.…”
Section: Box 1 Biofilm: What You Need To Knowmentioning
confidence: 99%
“…Nursing students often do not have sufficient knowledge about contemporary guidelines, preventing utilisation once they begin practicing in healthcare environments [ 3 , 7 , 12 ]. It is important for nursing students to have sufficient knowledge, skills, and positive attitudes on completion of educational preparation to prevent pressure injuries, and if necessary, to recognise, assess, and treat these wounds properly [ 8 , 13 ]. It is important to identify widely spread misconceptions and evaluate educational needs about pressure injury prevention to develop strategies for improving the quality of pressure injury education and prevention.…”
Section: Introductionmentioning
confidence: 99%